2010
DOI: 10.15283/ijsc.2010.3.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supermagnetic Iron Oxide Labeling on the Major Functional Properties of Human Mesenchymal Stem Cells from Multiple Sclerosis Patients

Abstract: Background and Objectives: In the last few years, treatment protocols using mesenchymal stem cells (MSC) in various experimental models and human diseases have been investigated. MSCs are on the focus of stem cell research, since they are considered as a type of adult stem cells with low toxicity and acceptable side effects profile and they can be administered autologously. In addition several studies have revealed significant immunomodulatory properties of MSCs and a potential for transdifferentiation, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…MSCs transplantation alone has been applied and tested with strong indications of beneficial effects in animal models of MS [22,23,24,25], stroke [26,27], traumatic brain injury [28], PD [29], schizophrenia, and autism [30,31], with encouraging indications in pivotal clinical trials in MS and ALS patients [22,23,33,34,35]. Many of the beneficial effects of MSC have been shown to be mediated by humoral mechanisms and the secretion of neurotrophic and immunomodulatory factors [15,16,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs transplantation alone has been applied and tested with strong indications of beneficial effects in animal models of MS [22,23,24,25], stroke [26,27], traumatic brain injury [28], PD [29], schizophrenia, and autism [30,31], with encouraging indications in pivotal clinical trials in MS and ALS patients [22,23,33,34,35]. Many of the beneficial effects of MSC have been shown to be mediated by humoral mechanisms and the secretion of neurotrophic and immunomodulatory factors [15,16,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs produce a variety of neurogenic, neuroprotective, and immunomodulatory agents [15,16,17,18,19,20,21], and have been shown to induce beneficial effects when transplanted in EAE-mice [22,23,24,25], stroke [26,27], traumatic brain injury [28], Parkinson’s disease [29], schizophrenia, and autism [30,31] as well as increased neurogenesis in adult mice [32]. MSC transplantation also showed indications of efficacy in clinical trials in MS and ALS patients [22,23,33,34,35]. We use here secretions of MSCs of human origin, having the advantage of exploring its potential for future therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…SPIO labeling may impact the proliferation, metabolic activity, viability, and overall morphology of MSCs, limiting their use[ 43 ]. Interestingly, Feridex (SPIO), a commercial paramagnetic material, demonstrated no effect on the physiological properties of MSCs, proposing their possible usefulness in the clinical setting[ 72 ]. Overall, SPIO labeling has low sensitivity and cannot detect the presence of a small number of cells[ 68 ].…”
Section: Labeling Of Mscs With Imaging Reportersmentioning
confidence: 99%
“…Labeling cells with iron oxide particles using these methods had no significant effect on cell viability or on ability to differentiate and migrate (Ben-Hur et al, 2007), especially at low (but still MR-visible) doses. However, some studies with mesenchymal stem cells (Bulte et al, 2004) have found differentiation along some lineages can be impaired; other studies have seen no effect (Arbab et al, 2005b; Kassis et al, 2010). Each cell type that is labeled in this way should be evaluated for effects on cell function prior to conducting studies in vivo .…”
Section: Mri Of Exogenously Administered Npcsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSC) can be obtained from patient and the use of such autologous grafts should reduce the likelihood of rejection (Akgun et al, 2015). MSC can be harvested in the operating room, cultured and labeled, then reintroduced into the targeted area of the patient (Callera and de Melo, 2007; Kassis et al, 2010). The importance of using autologous MSCs has not been definitively established (Kode et al, 2009).…”
Section: Mri Of Exogenously Administered Npcsmentioning
confidence: 99%